The injection of a screw dislocation into a crystal: atomistics vs. continuum elastodynamics - Jonas,Verschueren; Gurrutxaga,Lerma B; Balint,DS; Dini,D; Sutton,AP (Journal of the Mechanics and Physics of Solids, 2016)
The injection (creation) process of a straight screw dislocation is compared atomistically with elastodynamic continuum theory. Amethod for injecting quiescent screw dislocations into a crystal of tungsten is simulated using non-equilibrium molecular dynamics.The resulting stress fields are compared to the those of elastodynamic solutions for the injection of a quiescent screw dislocation.A number of differences are found: a plane wave emission is observed to emanate from the whole surface of the cut used to createthe dislocation, affecting the displacement field along the dislocation line (z), and introducing displacement field componentsperpendicular to the line (along x and y). It is argued that, in part, this emission is the result of the finite time required to injectthe dislocation, whereby the atoms in the cut surface must temporarily be displaced to unstable positions in order to produce therequired slip. By modelling this process in the continuum it is shown that the displacements components normal to the dislocationline arise from transient displacements of atoms in the cut surface parallel to x and y. It is shown that once these displacements areincluded in the elastodynamic continuum formulation the plane wave emission in uzis correctly captured. A detailed comparisonbetween the atomistic and continuum models is then offered, showing that the main atomistic features can also be captured in thecontinuum.